Sistem Pendukung Keputusan Menggunakan Metode WASPAS Untuk Pemilihan Aplikasi Manajemen Bisnis dan Keuangan - Idrus Ramadhan; Nurhasan Nugroho; Hadi Kurniawanto; Joni Warta (LPPM STIKI MALANG, 2024)
In dynamic and complex business environments, effective management is crucial, particularly in the use of business and financial applications. However, the plethora of available applications makes selecting the right one a complicated and time-consuming process. Users must review each application before making a decision, which is often difficult and lengthy due to a lack of comprehensive understanding of all available options. This research aims to develop a Decision Support System (DSS) utilizing the WASPAS (Weighted Aggregated Sum Product Assessment) method to facilitate the selection of ideal business and financial management applications and streamline the decision-making process. The WASPAS method is chosen for its ability to evaluate various alternatives by combining weighted sum and weighted product approaches, resulting in a more balanced and objective evaluation. This research produces a system capable of performing automatic calculations using the WASPAS method and presenting the best alternative recommendations in the form of rankings. Additionally, the DSS developed achieved an average usability score of 91.25%, indicating that the system is user-friendly and suitable for implementation